High-resolution CARMA observation of molecular gas in the North America and Pelican Nebulae - Kong, Shuo; Arce, Héctor G.; Carpenter, John M.; Bally, John; Ossenkopf-Okada, Volker; Sánchez-Monge, Álvaro; Sargent, Anneila I.; Suri, Sümeyye; McGehee, Peregrine; Lis, Dariusz C.; Klessen, Ralf S.; Mairs, Steve; et al. (The astronomical journal, 2021)
In this paper, we present the first results from a CARMA high-resolution 12CO(1-0), 13CO(1-0), and C18O(1-0) molecular line survey of the North America and Pelican (NAP) Nebulae. CARMA observations have been combined with single-dish data from the Purple Mountain 13.7 m telescope, to add short spacings and to produce high-dynamic-range images. We find that the molecular gas is predominantly shaped by the W80 H ii bubble, driven by an O star. Several bright rims noted in the observation are probably remnant molecular clouds, heated and stripped by the massive star. Matching these rims in molecular lines and optical images, we construct a model of the three-dimensional structure of the NAP complex. Two groups of molecular clumps/filaments are on the near side of the bubble: one is being pushed toward us, whereas the other is moving toward the bubble. Another group is on the far side of the bubble, and moving away. The young stellar objects in the Gulf region reside in three different clusters, each hosted by a cloud from one of the three molecular clump groups. Although all gas content in the NAP is impacted by feedback from the central O star, some regions show no signs of star formation, while other areas clearly exhibit star formation activity. Additional molecular gas being carved by feedback includes cometary structures in the Pelican Head region, and the boomerang features at the boundary of the Gulf region. The results show that the NAP complex is an ideal place for the study of feedback effects on star formation.